Development and validation of a VISA tendinopathy questionnaire for greater trochanteric pain syndrome, the VISA-G. Issue 6 (December 2015) - Fearon, A.M.; Ganderton, C.; Scarvell, J.M.; Smith, P.N.; Neeman, T.; Nash, C.; Cook, J.L.
Abstract: Background: Greater trochanteric pain syndrome (GTPS) is common, resulting in significant pain and disability. There is no condition specific outcome score to evaluate the degree of severity of disability associated with GTPS in patients with this condition. Objective: To develop a reliable and valid outcome measurement capable of evaluating the severity of disability associated with GTPS. Methods: A phenomenological framework using in-depth semi structured interviews of patients and medical experts, and focus groups of physiotherapists was used in the item generation. Item and format clarification was undertaken via piloting. Multivariate analysis provided the basis for item reduction. The resultant VISA-G was tested for reliability with the inter class co-efficient (ICC), internal consistency (Cronbach's Alpha), and construct validity (correlation co-efficient) on 52 naïve participants with GTPS and 31 asymptomatic participants. Results: The resultant outcome measurement tool is consistent in style with existing tendinopathy outcome measurement tools, namely the suite of VISA scores. The VISA-G was found to be have a test-retest reliability of ICC2, 1 (95% CI) of 0.827 (0.638–0.923). Internal consistency was high with a Cronbach's Alpha of 0.809. Construct validity was demonstrated: the VISA-G measures different constructs than tools previously used in assessing GTPS, the Harris Hip Score and the Oswestry Disability Index (Spearman Rho:0.020 and 0.0205 respectively). The VISA-G did not demonstrate any floor or ceiling effect in symptomatic participants. Conclusion: The VISA-G is a reliable and valid score for measuring the severity of disability associated GTPS. Highlights: The VISA-G is the first tool specifically designed to measure the severity of disability associated with GTPS. The VISA-G has been tested on a broad range of people from urban and regional Australia. The VISA-G has excellent reliability and validity: it has good generalizability in these populations.